Expanding Characterized Diversity and the Pool of Complete Genome Sequences of Methylococcus Species, the Bacteria of High Environmental and Biotechnological Relevance - Oshkin, Igor Y.; Danilova, Olga V.; But, Sergey Y.; Miroshnikov, Kirill K.; Suleimanov, Ruslan Z.; Belova, Svetlana E.; Tikhonova, Ekaterina N.; Kuznetsov, Nikolai N.; Khmelenina, Valentina N.; Pimenov, Nikolai V.; Dedysh, Svetlana N. (Frontiers in Microbiology, 2021)
The bacterial genus Methylococcus, which comprises aerobic thermotolerant methanotrophic cocci, was described half-a-century ago. Over the years, a member of this genus, Methylococcus capsulatus Bath, has become a major model organism to study genomic and metabolic basis of obligate methanotrophy. High biotechnological potential of fast-growing Methylococcus species, mainly as a promising source of feed protein, has also been recognized. Despite this big research attention, the currently cultured Methylococcus diversity is represented by members of the two species, Mc. capsulatus and Mc. geothermalis, while finished genome sequences are available only for two strains of these methanotrophs. This study extends the pool of phenotypically characterized Methylococcus strains with good-quality genome sequences by contributing four novel isolates of these bacteria from activated sludge, landfill cover soil and freshwater sediments. The determined genome sizes of novel isolates varied between 3.2 and 4.0 Mb. As revealed by the phylogenomic analysis, strains IO1, BH and KN2 affiliate with Mc. capsulatus, while strain Mc7 may potentially represent a novel species. Highest temperature optima (45-50°C) and highest growth rates in bioreactor cultures (up to 0.3 h-1) were recorded for strains obtained from activated sludge. The comparative analysis of all complete genomes of Methylococcus species revealed 4485‬ gene clusters. Of these, pan-genome core comprised 2331 genes (on average 51.9% of each genome), with the accessory genome containing 846 and 1308 genes in the shell and the cloud, respectively. Independently of the isolation source, all strains of Mc. capsulatus displayed surprisingly high genome synteny and a striking similarity in gene content. Strain Mc7 from a landfill cover soil differed from other isolates by the high content of mobile genetic elements in the genome and a number of genome-encoded features missing in Mc. capsulatus, such as sucrose biosynthesis and the ability to scavenge phosphorus and sulfur from the environment.